Halal certification mark, brand quality, and awareness: do they influence buying decisions of Nigerian consumers? - Jaiyeoba, Haruna Babatunde; Abdullah, Moha Asri (2019)
Purpose – This paper intends to ascertain whether halal certification mark, halal brand quality, and halal awareness influence Nigerian consumers when making buying decisions.